Hidden Attractors in Chaotic Systems with Nonlinear Functions - Safara Bibi; Juan Hugo García López; Rider Jaimes-reategui; Hafiz Muhammad Zeeshan; Guillermo Huerta-cuellar (Chaos Theory and Applications)
In the present work, an interesting mini-review of hidden attractors in dynamical systems with associated nonlinear functions is carried out. Chaotic systems with nonlinear functions often possess hidden attractors due to their inherent complexity. These attractors can arise in various mathematical models, such as the Lorenz system, Rössler system, or Chua's circuit. The identification and comprehension of hidden attractors broaden our understanding of complex systems and provide new directions for future study and technological development. The discovery and characterization of hidden attractors in chaotic systems have profound implications for various scientific disciplines, including physics, biology, and engineering.